Movements of older adults during exergaming interventions that are associated with the Systems Framework for Postural Control: A systematic review. (May 2018) - Tahmosybayat, Robin; Baker, Katherine; Godfrey, Alan; Caplan, Nick; Barry, Gill
Highlights: The totality of postural control is not currently trained in exergaming interventions. The choice of exergame console and game influence the areas of postural control trained. Sensory integration and reactive postural control is not currently trained using exergames. Exergames that utilise a changing base of support better meet the requirements for training postural control. Abstract: One in three older adults fall annually, in part due to impairments in the physiological systems that make up the postural control (PC) system. Exercise, particularly balance training, helps to prevent deterioration and even to improve outcomes in the PC system. Exergaming (exercise-gaming) is interactive computer gaming whereby an individual moves the body in response to onscreen cues in a playful format. Exergaming is an alternative method to standard practice for improving PC outcomes, which has been shown to reduce the risk of falling. Exergaming has received research attention, yet the intervention is still in its infancy. There could be benefit in exploring the movements trained with respect to a framework known for identifying underlying deficits in the PC system, the Systems Framework for Postural Control (SFPC). This may help target areas for improvement in balance training using exergames and shed light on the impact for fall prevention. A literature search was therefore conducted across six databases (CINAHL, EMBASE, PubMed, ISI, SPORTdiscus and Science Direct) using a range of search terms and combinations relating to exergaming, balance, exercise, falls and elderly. Quality assessment was conducted using the PEDro Scale and a custom-made quality assessment tool. Movements were rated by two reviewers based on the 9 operational definitions of the SFPC. Eighteen publications were included in the analysis, with a mean PEDro score of 5.6 (1.5). Overall, 4.99 (1.27) of the 9 operational definitions of the SFPC are trained in exergaming interventions. Exergaming does encourage individuals to stand up (3), lean while standing (4), move upper limbs and turn heads (6) and dual-task while standing (9), to some extent move the body forwards, backwards and sideways (1), and coordinate movements (2) but hardly at all to kick, hop, jump or walk (7), or to force a postural reaction from a physical force to the individual (5) and it does not mimic actual changes in sensory context (8). This is the first review, to our knowledge, that synthesises the literature on movements trained in exergaming interventions with respect to an established theoretical framework for PC. This review could provide useful information for designing exergames with PC outcomes in mind, which could help target specific exergames for multi-factorial training to overcome balance deficits. Some elements of PC are too unsafe to be trained using exergames, such as restricting sensory inputs or applying physical perturbations to an individual to elicit postural responses.